2016
DOI: 10.1002/iub.1557
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of arginine and its “Downstream” molecules as potential markers of breast cancer

Abstract: SummaryBreast cancer (BC) is the most commonly diagnosed cancer in women worldwide. Arginine is a semiessential amino acid in humans and is essential for several biological pathways in malignant and normal cells, such as ornithine and N1, N12-diacetylspermine (DiAcSpm). This study aimed to determine the role of arginine and these downstream molecules in BC. Plasma arginine, ornithine, and arginine-to-ornithine ratio (AOR) were analysed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Urine samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…ER‐positive BC patients tended to have lower levels of arginine than ER‐negative BC patients. The result was diametrically opposed to the previous reports , so that more studies were needed to verify the conclusion. ER is expressed in 75% of BC overall and is the major driver in the majority of BC, with nuclear and non‐nuclear functions .…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…ER‐positive BC patients tended to have lower levels of arginine than ER‐negative BC patients. The result was diametrically opposed to the previous reports , so that more studies were needed to verify the conclusion. ER is expressed in 75% of BC overall and is the major driver in the majority of BC, with nuclear and non‐nuclear functions .…”
Section: Discussioncontrasting
confidence: 92%
“…Arginine auxotrophs are cells that lack active ASS1, the enzyme catalysing the final step in arginine biosynthesis , and that have lost the ability to synthesise arginine and have to rely on external arginine sources. The decrease in plasma arginine levels has been described in BC patients in previous studies . In addition, increased levels of arginine have been observed in breast tumours tissues compared to benign breast tissues .…”
Section: Discussionsupporting
confidence: 54%
“…Studies showing that changes in arginine metabolism are important in a variety of diseases such as sepsis, cancer and type II diabetes also support our findings ( 27 , 28 , 29 ). In another study supporting our findings, it was suggested that arginine/ornithine ratio (AOR) decreased in breast cancer patients and this could be a marker ( 30 ). The ornithine levels in all of the study groups were increased and statistically significant ( Table 3 ).…”
Section: Discussionsupporting
confidence: 86%
“…The difference is very significant when it is based on diabetes. Although an increase in the levels of polyamines in cancer appears to be a natural result ( 30 , 33 , 34 ), an increase in the levels of enzymes responsible for polyamine synthase pathway in breast cancer developing in the presence of diabetes is a significant finding.…”
Section: Discussionmentioning
confidence: 99%
“…N1, N12-diacetylspermine is an amine metabolic compound known to be a urine tumor biomarker. Increased urine concentrations of N1, N12-diacetylspermine occurs in many types of cancers (e.g., breast cancer [ 17 , 18 ], colorectal cancer [ 18 ], non-small cell lung cancer [ 19 ], bladder cancer [ 20 ], metastatic and primary brain tumors including grade 3 and 4 gliomas and primary CNS lymphoma [ 21 ], hepatocellular carcinoma [ 22 ], and leukemia [ 23 ]). To the best of our knowledge, our results are the first to suggest that the CSF concentrations of N1, N12-diacetylspermine might be useful for selecting patients with cancers or brain tumors.…”
Section: Discussionmentioning
confidence: 99%